On the black hole inner mechanics - Giribet, Gaston Enrique (2012)
With the aim of investigating to what extent the statement of the recently proposed laws of black hole inner mechanics hold, here I study the case of higher-curvature theories of gravity. I focus my attention on certain gravity theories that emerge in the low energy limit of string theory. I prove that, in such a scenario, one of the statements of the black hole inner mechanics -the statement about the product of entropies associated to black hole horizons resulting independent of the mass- does not hold. I make use of this observation to speculate about the origin of the quantization of mass.